2007
DOI: 10.1038/sj.ijo.0803644
|View full text |Cite
|
Sign up to set email alerts
|

Associations between obesity and developmental functioning in pre-school children: a population-based study

Abstract: Objective: To examine associations between obesity and impairment in developmental functioning in a general population sample of pre-school children. Method: Standardized medical examinations were conducted in nine consecutive cohorts of male and female children (n ¼ 9415) aged between 4.4 and 8.6 years (mean ¼ 6.0, s.d. ¼ 0.37) residing in the Lower Bavaria region of Germany. Tests designed to assess performance in subdivisions representing four broad developmental domains, namely, motor development, speech d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
7
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 35 publications
10
77
7
8
Order By: Relevance
“…This is consistent with two previous studies that found that obesity was associated with impaired developmental functioning or worse academic performance in boys but not girls (Datar et al 2004;Mond et al 2007). The labor market penalty for adult obesity is generally greater for women than men (Averett and Korenman 1996;Cawley, 2004;Lundborg et al 2007); this paper finds little if any evidence that the greater penalty is due to less human capital accumulation.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is consistent with two previous studies that found that obesity was associated with impaired developmental functioning or worse academic performance in boys but not girls (Datar et al 2004;Mond et al 2007). The labor market penalty for adult obesity is generally greater for women than men (Averett and Korenman 1996;Cawley, 2004;Lundborg et al 2007); this paper finds little if any evidence that the greater penalty is due to less human capital accumulation.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies of whether childhood overweight is associated with impaired developmental functioning have focused largely on children of elementary school age (Datar and Sturm,2006;Cairney et al 2006;Datar et al 2004;Graf et al 2004;Mosuwan et al 1999) or those about to enter elementary school (Mond et al, 2007). To our knowledge, this is the first study of overweight and developmental functioning to study children as young as 2 to 4 years old.…”
Section: Introductionmentioning
confidence: 91%
“…Zhu, Wu, & Cairney, 2011), (ii) these differences are particularly pronounced for (static and dynamic) balance (BL; D'Hondt, Deforche, De Bourdeaudhuij, & Lenoir, 2009;Zhu et al, 2011;in depth Graf et al, 2004) Deforche, De Bourdeaudhuij, & Lenoir, 2008), and (iii) these differences in balance are more pronounced in boys than in girls (Mond, Stich, Hay, Kraemer, & Baune, 2007; partially Cawley & Spiess, 2008;in contrast Zhu et al, 2011; in depth for boys Deforche et al, 2009b;Goulding, Jones, Taylor, Piggot, & Taylor, 2003).…”
Section: Empirical Evidence and Research Desideratamentioning
confidence: 95%
“…4 Similarly, Mo-suwan et al 5 found that an association between overweight status and poor school performance existed among Thai children from grades 7 --9. Mond et al 6 observed that the prevalence of impairment in gross motor skills was higher among obese than normal-weight boys, whereas the prevalence of impairment in the ability to focus attention was higher among the obese compared with normal-weight girls after controlling for age and other potential covariates among pre-school Germany children. A significant relationship between children's weight category and their reading/language arts, and mathematics test scores was revealed among 968 fifth grade students even after adjustment for a proxy of socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%